Characteristics of Objective Sleep and Its Related Risk Factors Among Parkinson's Disease Patients With and Without Restless Legs Syndrome - Sun, Shuyu; Zhao, Xianchao; Ren, Jiafeng; Cheng, Jinxiang; Zhou, Junying; Su, Changjun (Frontiers in Neurology, 2021)
Abstract Objective: This study aimed to investigate the objective sleep characteristics and their related risk factors among Parkinson’s disease (PD) patients with and without restless legs syndrome (RLS). Methods: 125 patients with PD who underwent overnight polysomnography (PSG) were recruited consecutively. Eighty-one patients, including 27 PD with RLS (PD-RLS) and 54 PD without RLS (PD-NRLS), were included in the final analysis after 1:2 propensity score matching. Demographic, clinical, and polysomnographic data were compared between PD patients with and without RLS. The risk factors for sleep quality were examined using a multiple linear regression model. Results: The prevalence of RLS among PD patients was 28.0% (35/125). The PD-RLS group exhibited a higher score for the Unified Parkinson Disease Rating Scale (UPDRS) III than the PD-NRLS group. Also, the PD-RLS patients displayed significantly shorter total sleep times, worse sleep quality, decreased stage 3 duration, a longer wake time after sleep onset, and a higher arousal index than those without RLS (all p  0.05). In the multiple linear regression model, PD duration (β = -0.363, 95% CI: -0.652 to -0.074; p = 0.016), UPDRS-III (β = -0.356, 95% CI: -0.641 to -0.071; p = 0.016) and periodic limb movement index (PLMI) (β = -0.472, 95% CI: -0.757 to -0.187; p = 0.002) were determined to be the risk factors influencing sleep quality in PD-RLS patients. The UPDRS-III (β = -0.347, 95% CI: -0.590 to -0.104; p = 0.006) and HAMD scores (β = -0.343, 95% CI: -0.586 to -0.100; p = 0.007) were significantly associated with sleep quality after adjusting for confounding factors in PD-NRLS patients, respectively. Conclusions: PD-RLS patients exhibited more disturbed and fragmented sleep in objective sleep architecture than PD-NRLS patients. The severity of motor symptoms in PD was significantly associated with poor sleep quality in both PD-RLS and PD-NRLS patients. Notably, our findings indicated that periodic limb movements during sleep (PLMS) was the risk factor that influenced the objective sleep quality in PD patients with RLS.